2020
DOI: 10.1002/admt.202000584
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dual‐Split‐Disk Resonator with Electromagnetically Induced Transparency Characteristic

Abstract: A tunable dual‐split‐disk resonator (TDSDR) composed of top and bottom Au split‐disk resonators (SDRs) in the terahertz (THz) wave is presented. TDSDR exhibits electromagnetically induced transparency (EIT) characteristic by changing the rotation angle of top SDR (θ) and distance between top and bottom SDRs (h). The bright and dark modes are defined by the resonances with θ = 90° and 0°, respectively. The resonances could also be controlled by changing h values. It can generate a tunable sharp resonance by mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Let us take the third TE resonance (TE: ω 3 , green line) as an example, then the maximum, minimum, and average values of the calculated Q-factors are 72.47, 59.91, and 66.01, respectively, while the corresponding calculated FOMs values are 71.33, 56.49, and 63.83, respectively. The sensing performances of this design are better than those reported in literature reports [ 9 , 15 , 51 ] as summarized in Table 2 . Therefore, the proposed MEMS-based TTM device could be suitably used in environment sensing fields, such as gas sensing, bio-sensing, and chemical sensing, etc.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Let us take the third TE resonance (TE: ω 3 , green line) as an example, then the maximum, minimum, and average values of the calculated Q-factors are 72.47, 59.91, and 66.01, respectively, while the corresponding calculated FOMs values are 71.33, 56.49, and 63.83, respectively. The sensing performances of this design are better than those reported in literature reports [ 9 , 15 , 51 ] as summarized in Table 2 . Therefore, the proposed MEMS-based TTM device could be suitably used in environment sensing fields, such as gas sensing, bio-sensing, and chemical sensing, etc.…”
Section: Resultsmentioning
confidence: 56%
“…In the recent years, there have been many investigations and reports in various potential applications of metamaterials, such as cloaking devices, high-sensitive environment sensors, perfect absorbers, security screening, tunable ultrahigh-speed filters, imaging devices, high-efficient light emitters, and non-destructive testing [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Metamaterials show many unique electromagnetic properties including field enhancement [ 11 , 12 ], negative refraction index [ 13 ], artificial magnetism [ 14 ], electromagnetically induced transparency (EIT) [ 15 ], and so on. By properly tailoring the geometric parameters, metamaterials are able to be easily operated in a wide spectrum range that includes terahertz (THz), infrared (IR), and visible light [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the targeted gases mentioned above have their absorption features in this area of the electromagnetic field [ 14 , 15 , 16 , 17 , 18 , 19 ], as one can see in Figure 1 . Mid-IR gas sensor types are different in cost and efficiency, depending on their configuration [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some of the most sensitive systems (sensitivity up to parts-per-trillion concentration), such as the mid-infrared sensor system based on continuous-wave (CW) interband cascade laser (ICL) [ 16 ], or those based on Tuneable Diode Laser Absorption Spectroscopy (TDLAS), Quartz-Enhanced Photoacoustic Spectroscopy (QEPAS) [ 15 ], include laser as emitting sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported as an alternative to laser-based gas sensors IR quasi-monochromatic sources that use “perfect” absorbers based on metamaterial [ 20 , 21 , 22 , 23 , 24 , 29 , 30 ]. The advantage of this type of IR source is the wavelength selectivity, having the possibility to be tuned within UV up to the THz range, only by changing the type of material and the geometrical configuration [ 22 , 25 , 26 , 27 ]. Besides that, the compatibility of metamaterials with classic fabrication processes (such as photolithography and lift-off) has been proved recently, minimizing the production costs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many derivative structures have demonstrated—such as I-shaped SRR, U-shaped SRR, and 3D-SRR, and complementary structures [ 13 , 14 , 15 , 16 , 17 , 18 ]—which can be used to span the visible [ 19 , 20 ], infrared [ 21 , 22 ], and THz [ 23 , 24 , 25 ] spectra ranges. The electromagnetic characteristics of various metamaterials are Fano resonance [ 26 ], electromagnetically induced transparency effect [ 27 ], and spoof surface plasmons [ 28 , 29 ]. In view of the above merits of metamaterial, it can be used in widespread applications—such as absorbers [ 30 ], invisibility cloaks [ 20 ], filters [ 31 ], sensors [ 32 ], and so on.…”
Section: Introductionmentioning
confidence: 99%